TREN PERSAINGAN VENDOR ENTERPRISE RESOURCE PLANNING (ERP) DALAM BISNIS GLOBAL - arista Qiyamullailiy; Yusuf Amrozi (Jurnal Teknologi Informasi: Jurnal Keilmuan dan Aplikasi Bidang Teknik Informatika, 2021)
There are still some companies that do not apply ERP with company/organizational processing. ERP implementation is very important for companies, therefore it is necessary to find the right vendor to be applied to the company. So this research is needed to find out which vendors are most widely used in global business. The method used in this research is to find data in the literature and related journals. This research results in an ERP vendor that relatively dominates the market is SAP.